BEHAVIORISM OR MENTALISM? THE CASE OF FOREIGN LANGUAGE LEARNING PROCESS IN MODERN ISLAMIC BOARDING SCHOOLS - Faiz Rizki Muhammad; M. Ashadi (IJIET (International Journal of Indonesian Education and Teaching), 2019)
There are two majorities of thought in the process of language learning and acquisition. They are behaviorist and mentalist theory. The behaviorist theory is based on psychological aspects of learners in their habit formation while the mentalist’s come with the new approach called Language Acquisition Device (LAD) that used in the process of learning. In Modern Islamic Boarding School the term of language environment is used as the process of foreign language learning in which students communicate one another by using the foreign languages, but they are also forced to learn their structures and systems in the classes. The researcher used ethnography and narrative study to gain the data, he observed the phenomenon directly to the one most prominent Modern Islamic Boarding School located in East Java and interviewed with the responsible teacher for language development, in conclusion, both theories are used by Modern Islamic Boarding School in the process of language learning.